THE RELATIONSHIP BETWEEN SELF-CARE MANAGEMENT AND DIABETES FOOT ULCER RISK AMONG TYPE 2 DIABETES PATIENTS - Hermanto, Hermanto; Salustiano, Salustiano (LPPM STIKES KENDAL, 2019)
Diabetes is a disease that leads to death in developing countries including Indonesia.  Diabetic Foot Ulcers (DFU) is one of the clinical complications that result from the degenerative changes through the body.  The purpose of the study is to examine relationship between degree of self-care management and diabetes foot ulcer risk among type 2 diabetes patients.  In this study, the investigator utilized the quantitative research method with correlation design using cross-sectional approach.  With the computed value 0.000 lower than p value at 0.05 significant level statistical data analysis revealed a significant relationship between level of self-care management and foot ulcer risk.  The level of self-care management has strong influence on foot ulcer risk; better self-care management leads to lower risk of foot ulcer in type 2 diabetes patients.